Targeted modification of CmACO1 by CRISPR/Cas9 extends the shelf-life of Cucumis melo var. reticulatus melon - Nonaka, Satoko; Ito, Maki; Ezura, Hiroshi (Frontiers in Genome Editing, 2023)
The gaseous plant hormone ethylene is a regulator of fruit shelf-life, one of the essential traits in fruits. Extending fruit shelf-life reduces food loss, thereby expected to contribute to food security. The enzyme 1-aminocyclopropane-1-carboxylic acid oxidase (ACO) is the final step of the ethylene production pathway. Its suppression via antisense technology has been demonstrated to extend the shelf-life of melon, apple, and papaya. Genome editing technology is an innovative technique for plant breeding. Because the genome editing technology would not leave the exogenous genes in the final crop products, the crops via genome editing can be considered non-genetically modified yields; compared to conventional breeding, such as mutation breeding, the breeding term would be expected to be relatively short. These points include the advantage of this technique in utilization for commercial applications. We attempted to extend the shelf-life of the Japanese luxury melon (Cucumis melo var. reticulatus, ‘Harukei-3’) via modification of the ethylene synthesis pathway with the genome editing technology, CRISPR/Cas9 system. The Melonet-DB (https://melonet-db.dna.affrc.go.jp/ap/top) showed that the melon genome had the five CmACOs and the gene CmACO1 predominantly expressed in harvested fruits. From this information, CmACO1 was expected to be a key gene for shelf-life in melons. Based on this information, the CmACO1 was selected as the target of the CRISPR/Cas9 system and introduced the mutation. The final product of this melon did not have any exogenous genes. The mutation was inherited for at least two generations. In the T2 generation, the fruit phenotypes 14 days after harvest were as follows: ethylene production was reduced to one-tenth that of the wild type, pericarp colour remained green, and higher fruit firmness. Early fermentation of the fresh fruit was observed in the wild-type fruit but not in the mutant. These results show that CmACO1 knockout via CRISPR/Cas9 extended the melon’s shelf-life. Moreover, our results suggest that genome editing technology would reduce food loss and contribute to food security.